Comparison of MB-Check, BACTEC, and egg-based media for recovery of mycobacteria. - Abe, C (1992)
The rate of recovery and time to the detection of mycobacteria from clinical specimens were measured for biphasic (MB-Check; Nippon Roche Co., Ltd., Tokyo, Japan) and radiometric (BACTEC; Nippon Becton Dickinson Co., Ltd., Tokyo, Japan) liquid-based culture systems and egg-based media (3% Ogawa and Ogawa K). From the 245 sputum specimens processed, a total of 86 (35.1%) mycobacterial isolates were detected. Of these, 81 (94.2%) and 80 (93.0%) isolates were detected with the MB-Check and BACTEC systems, respectively, and 65 (75.6%) isolates were detected with the 3% Ogawa egg method. The difference in the percentages of positive cultures between the two systems based on liquid media and the 3% Ogawa egg method was significant (P less than 0.01). This difference was even greater among smear-negative specimens. The detection time was shorter with the liquid-based systems. The mean times to the detection of the Mycobacterium tuberculosis complex were 19.1 days with the MB-Check system, 13.4 days with the BACTEC system, and 21.7 days with the 3% Ogawa egg method. These results indicate that both the MB-Check and the BACTEC systems, based on liquid media, are efficient for the recovery of mycobacteria.